STATISTICAL RESULTS OF THE EFFECTIVENESS OF THE PROGRAM OF PSYCHOLOGICAL SERVICES FOR PARENTS OF CHILDREN WITH SPECIAL NEEDS IN THE GROUPS OF «MUTUAL ASSISTANCE» - Ostrovskaya, Katerina; Andreiko, Bogdanya (PSYCHOLOGICAL JOURNAL, 2017)
The program of psychological assistance for parents in the group of psychological support for parents consists of stages that go alternately. Stages of work: informative, diagnostic, psychological and consultative, psychotherapeutic. Important, for today, there is a clear understanding of the problem in the absence of psychological assistance to parents of children with special needs. The article analyzes the theory and method of social psychological work with the family. After working out theoretical foundations and psychological studies of working with parents of children with special needs, we form a complex complex of work with parents aimed at correction and stabilization of emotional states in parents, psychotherapeutic work on the personality-motivational sphere, work on family-related relationships. In this work, we used the basics and techniques of individual and psychological counseling and therapy BSFT. The article describes in detail and in stages the work and process of short-term therapy. The importance and necessity of this paradigm of services in the sphere of disability is substantiated and the efficiency of work is statistically proved.